Poster of time-series forecasting analysis on dental treatment need of first visit patient at IIUM Dental Outpatient Clinic (Periodontal and Conservative Department) for the year 2017 and 2018 - Ismail, Azlini; Musa, Syazalina; Abllah, Zurainie; Muhammad Radhi, Nur Aishah (2020)
This poster has been created by the inventor and checked by the co-inventor for participating in a local scientific conference, 7th Dental Student's Scientific Conference Kulliyyah of Dentistry, International Islamic University Malaysia, Kuantan, Pahang on 26th February 2018.